1991
DOI: 10.1007/bf01744265
|View full text |Cite
|
Sign up to set email alerts
|

Local effects of impaired mechanical properties of collagen on bone formation and resorption

Abstract: To study the relationship between the mechanical properties of collagen and the bone turnover, 2-week-old Balb/C mice were fed on a diet containing 0.25% Beta aminopropionitrile (B-APN), a potent inhibitor of collagen crosslink formation, for 3 weeks. Mandibular incisor socket was selected for the analysis of bone formation and resorption parameters. Plastic embedded sections stained with toluidine blue and cut at 4 microns were used to analyze the average area of bone lamellae, bone-forming surface, and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These factors could also explain the difference in the effects on osteoclasts between in vitro and in vivo. In previous studies, an increase in the number of osteoclasts was observed following the administration of BAPN at the alveolar bone surface in mice [ 40 ] and rats [ 37 ]. It has been reported that the turnover rate of alveolar bone is faster than that of femur [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors could also explain the difference in the effects on osteoclasts between in vitro and in vivo. In previous studies, an increase in the number of osteoclasts was observed following the administration of BAPN at the alveolar bone surface in mice [ 40 ] and rats [ 37 ]. It has been reported that the turnover rate of alveolar bone is faster than that of femur [ 41 ].…”
Section: Discussionmentioning
confidence: 99%